Comparative analysis of the complete plastomes of nine Pimpinella species (Apiaceae) from China - Zhixin Wang; Limin Cao; Jianhui Liu; Xingjin He (PeerJ, 2023)
Pimpinella L. is one of the large genera in the Apiaceae family. In a previous study, the molecular phylogenies of Pimpinella were explored using nuclear ribosomal DNA internal transcribed spacers (ITS) and several chloroplast DNA segments. There have been few studies conducted on chloroplast genomes in Pimpinella, which has limited systematic understanding of this genus. We assembled the complete chloroplast genomes of nine Pimpinella species from China using data generated from next generation sequencing (NGS). The chloroplast (cp) DNA used were standard double-stranded molecules, ranging from 146,432 base pairs (bp) (P. valleculosa) to 165,666 bp (P. purpurea) in length. The circular DNA contained a large single-copy (LSC) region, small single-copy (SSC) region, and pair of inverted repeats (IRs). The cp DNA of the nine species contained 82–93 protein-coding genes, 36–37 transfer RNA (tRNA) genes, and eight ribosomal RNA (rRNA) genes, respectively. Four species (P. smithii, P. valleculosa, P. rhomboidea, and P. purpurea) exhibited striking distinctions in genome size, gene number, IR boundary, and sequence identity. We confirmed the non-monophyly of the Pimpinella species on the basis of the nine newly identified plastomes. The distant relationship between the above-mentioned four Pimpinella species and Pimpinelleae was indicated with high support values. Our study provides a foundation for future in-depth phylogenetic and taxonomic studies of genus Pimpinella.